2004
DOI: 10.1590/s0100-39842004000600009
|View full text |Cite
|
Sign up to set email alerts
|

Análise retrospectiva das urografias excretoras em um serviço de radiologia de um hospital geral

Abstract: OBJETIVO: Fazer uma revisão de 225 exames de urografia excretora, analisando estatisticamente as principais alterações relacionadas com o trato urinário, e reafirmar a utilidade do método. MATERIAIS E MÉTODOS: Estudo retrospectivo e descritivo realizado a partir de levantamento de 225 exames de urografia excretora realizados no período de 2/1/2002 a 29/11/2002, no Serviço de Radiologia do Hospital Santa Cruz da Beneficência Portuguesa de Niterói. RESULTADOS: Do total de 225 exames, 173 (76,9%) apresentaram alt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
1
1
Order By: Relevance
“…The advent of CT and MRI has led to less use of the cheaper, less invasive and affordable radiological technique for the investigation of the urinary tract. 2 The present finding that the patients subjected to IVU showed equal number of males and females which is in contrast to those reported from Jordan and Pakistan as well as Hameed M. Aklan and Abdullah Mikhlafy 3,4 , their study reported about two-thirds of the patients being males their figures are 60.0%, 63.0% and 66.8% respectively. However, it is in contrast to a study reported from United States, where most cases were females (73.0%) 5 .…”
Section: Discussioncontrasting
confidence: 89%
“…The advent of CT and MRI has led to less use of the cheaper, less invasive and affordable radiological technique for the investigation of the urinary tract. 2 The present finding that the patients subjected to IVU showed equal number of males and females which is in contrast to those reported from Jordan and Pakistan as well as Hameed M. Aklan and Abdullah Mikhlafy 3,4 , their study reported about two-thirds of the patients being males their figures are 60.0%, 63.0% and 66.8% respectively. However, it is in contrast to a study reported from United States, where most cases were females (73.0%) 5 .…”
Section: Discussioncontrasting
confidence: 89%
“…In this index study, normal IVU was 16, this is near 23.1%, 26.0% and 31.2% in Pakistan, Brazil and Yemen 11,[7][8] respectively. This contradicts a report submitted by Little MA et al 5 (77.0%).…”
Section: Discussionmentioning
confidence: 59%